Construction Design, Modelling, and Parameter Computation Outer Rotor Induction Motor - Faizal Ramadhan Putra; Eka Iskandar; Rusdhianto Abdul Kadir; Ari Santoso; Yusuf Bilfaqih; Mohamad Abdul Hady (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
In this paper, we will discuss the construction design of an outer rotor induction motor that can be applied to an electric car that is installed inside the car's wheels. In designing a motor, it is necessary to pay attention to the motor parameters, both mechanical parameters, and electrical parameters. These parameters will be calculated using software and designed in such a way as to get the parameters that are as effective and efficient as possible for the use of electric cars. After obtaining the best design, a comparison of the simulation results with mathematical modeling will be seen. In this research project, we can get a design with an initial torque of 64 Nm for a speed limit of 25 km/hour. Keywords: construction, induction, in-wheel, motor, outer rotor.